Peripheralizing core labour markets? : the case of the Canadian meat packing industry - Novek, Joel [Verfasser] (My University, 1989)
"Recent debates in the sociology of work and employment have drawn a pessimistic picture of the leading mass production industries in the advanced nations and the core labour markets they sustain. It has been claimed that such industries are in decline and that their workers face an assault on their jobs, wage levels and working conditions. The Canadian meat packing industry has been selected as a case study of a mass production industry and a core labour market under the stress of recessionary restructuring. In that industry, changes in production technology, markets and industrial organization are contributing to a reduction in employment, relative wage levels and working conditions. The costs of a more uncertain economic environment have been transferred to the labour force. However, meat packing remains in essence a mass production industry whose problems are as much industry-specific as they are an instance of wider global trends." (author's abstract) ((en)) Am Beispiel der fleischverarbeitenden Industrie in Kanada setzt sich der Beitrag mit dem Zusammenhang von Wirtschaftskrise, Wandel der Produktionsstrukturen und Beschäftigung auseinander. Dabei wird Bezug genommen auf die Diskussion über Massenproduktion und neue Produktionskonzepte, Kern- und Randbelegschaften sowie technischen Wandel und veränderte Machtbedingungen. Die Beschäftigung wird in Hinblick auf Personalabbau, Lohnniveau und Arbeitsbedingungen analysiert. (IAB)
Die Persipherisierung von Kernarbeitsmärkten am Beispiel der fleischverarbeitenden Industrie Kanadas
Keywords: G 1.2.4.1.4 Verarbeitendes Gewerbe; G 1.2.4.1 Produktion und Gewinnung; G 2.3.5 Wirtschaftsstrukturwandel; S 6.2.5 Ernährungsberufe; G 1.2.2.1 Lohn- & Tarifsysteme; G 2.3.1 Arbeitsteilung & -organisation; Nahrungs- und Genussmittelgewerbe; Produktion; Strukturwandel; Fleischverarbeiter; Dezentralisation; Lohnhöhe; Arbeitsbedingungen; Personalabbau; Berufsproblem